Recruitment of the Nuclear Form of Uracil DNA Glycosylase into Virus Particles Participates in the Full Infectivity of HIV-1 - Guenzel, Carolin A. (American Society for Microbiology, 2012)
The HIV-1 Vpr protein participates in the early steps of the virus life cycle by influencing the accuracy of reverse transcription. This role of Vpr was related to the recruitment of the nuclear form of the uracil DNA glycosylase (UNG2) enzyme into virus particles, but several conflicting findings have been reported regarding the role of UNG2 encapsidation on viral infectivity. Here, we report that the catalytic activity of UNG2 was not required for influencing HIV-1 mutation, and this function of UNG2 was mapped within a 60-amino-acid domain located in the N-terminal region of the protein required for direct interaction with the p32 subunit of the replication protein A (RPA) complex. Importantly, enforced recruitment of overexpressed UNG2 into virions resulted in a net increase of virus infectivity, and this positive effect on infectivity was also independent of the UNG2 enzymatic activity. In contrast, virus infectivity and replication, as well as the efficiency of the viral DNA synthesis, were significantly reduced when viruses were produced from cells depleted of either endogenous UNG2 or RPA p32. Taken together, these results demonstrate that incorporation of UNG2 into virions has a positive impact on HIV-1 infectivity and replication and positively influences the reverse transcription process through a nonenzymatic mechanism involving the p32 subunit of the RPA complex.